Modelling Cooperative Control Problems in the Cyber Environment: Introduction to Quasi Consensus Networks - Edelmayer, A.; Virág, L.; Kovács, J. (Acta Technica Jaurinensis, 2013)
The paper introduces the novel idea of the application of quasi consensus networks to modelling networked distributed systems. Quasi consensus networks operate alike standard consensus seeking ones without requesting the information state of the contributing systems to converge to a predetermined value. The quasi consensus-modelling paradigm can be used in modelling cooperative control problems in the cyber environment when the achievement of a common value of the information state is not the ultimate goal of the systems operation.